Perancangan Campaign dan Media Promosinya untuk Meningkatkan Brand Awareness Hobee - Marcelina Hartono; Marina Wardaya (Universitas Ciputra Surabaya, 2022)
The pandemic has been a highlight for the last three years and has changed many aspects of life. Life is not the same anymore, people have to shift and adjust their lifestyles due to the pandemic, and mental health is also affected by this phenomenon. Studies show that the stress level is increasing due to pandemic, it happens along with the rules to limiting activities outside the home. To overcome it, many people look for alternative activities to reduce stress and spend time productively. Hobbies have many positive impacts and can be a stress reliever, another advantage of having a hobby is it's easier to create connections with individuals who have similar interests, self-development, and skill improvement. However, because many people are still confused about where to start a hobby, and buying the equipment separately will cost more money and if it probably won’t be necessarily be pursued for a long time, Hobee is comes up as a solution by providing a complete starter kit for beginners who are exploring their interests. Hobee need a branding strategy that can create brand awareness, so that Hobee's mission and values ​​can be acknowlegde by the audience. Instagram was chosen as a medium to develop Hobee's branding because Instagram has many features that support business and make it easier for Hobee to reach wider market so that the brand can be recognized. This research conducted using data collection methods in the form of interviews, surveys, and literature studies. The research is carried out to find out what content is appealing to the audience the most, and effective for Hobee to build its branding and promotion, and also to help Hobee determining an approach to the audience. Therefore, by designing Hobee, teenagers and young adults can be facilitated by Hobee's educational content and Hobee’s products in developing interests and skills. Keywords: Branding, Brand Awareness, Promotion, Education, Hobby